Design and Analysis of a Novel Composited Electromagnetic Linear Actuator - Xinyu Fan; Jie Yin; Qinfen Lu (Actuators, 2021)
Electromagnetic linear actuators, as key executive components, have a vital impact on the performance of fully flexible variable valve trains. Considering that the conventional moving coil electromagnetic linear actuator (MCELA) has the disadvantages of low force density and a lack of end-passive self-holding ability, a novel composited electromagnetic linear actuator (CELA) is proposed by combining the performance advantages of MCELA and moving iron electromagnetic linear actuator (MIELA) in this work. Firstly, the structure and magnetic circuit design scheme of the proposed actuator are introduced and the finite element simulation model is established. The magnetic field distribution and force characteristics of the actuators are assessed by finite element simulation. Secondly, the construction of the prototype of the actuator is outlined, based on which the feasibility of the design scheme and the steady-state performance of the actuator are verified. Finally, the coordinated control strategy is proposed to realize the multi motion coordination control of the actuator. The research results show that the maximum starting force of the CELA with the end-passive self-holding ability is 574.92 N while the holding force can approach 229.25 N. Moreover, the CELA is proven to have excellent dynamic characteristics and control precision under different motion modes and to have an improved adaptability to the complex working conditions of internal combustion engines.